The Effect of Financing on Credit Risk: Empirically on Indonesian Islamic Banking - Fitri Zaelina; Dwi Nastiti (EkBis: Jurnal Ekonomi dan Bisnis, 2021)
Islamic banking has an important role in the economy, especially in moving the real sector. Islamic banking provides funding to the public in the form of financing. The financing provided cannot be separated from various risks that can threaten the health of the bank, one of which is financing risk. For that, the purpose of this study is to analyze the effect of financing on financing risk in Islamic banks for the period 2015 to 2020. The method used in this study is quantitative with multiple linear regression analysis techniques. This study uses time-series data and the variables in this study are mudharabah, musyarakah, murabahah, ijarah financing, and total assets as independent variables and NPF as a dependent variable. The results of the study concluded that total assets had a negative and significant effect on NPF and murabahah financing had a positive and significant effect on NPF. Meanwhile, mudharabah, musyarakah, and ijarah financing has no significant effect on NPF.